Survey-based Evaluation of Resident and Attending Financial Literacy - Ryan M. Huebinger (eScholarship Publishing, University of California, 2021)
Introduction: Physician finances are linked to wellness and burnout. However, few physicians receive financial management education. We sought to determine the financial literacy and educational need of attending and resident physician at an academic emergency medicine (EM) residency. Methods: We performed a cross-sectional, survey study at an academic EM residency. We devised a 49-question survey with four major domains: demographics (16 questions); Likert-scale questions evaluating value placed on personal finances (3 questions); Likert-scale questions evaluating perceived financial literacy (11 questions); and a financial literacy test based on previously developed and widely used financial literacy questions (19 questions). We administered the survey to EM attendings and residents. We analyzed the data using descriptive statistics and compared attending and resident test question responses. Results: A total of 44 residents and 24 attendings responded to the survey. Few (9.0% of residents, 12.5% of attendings) reported prior formal financial education. However, most respondents (70.5% of residents and 79.2% of attendings) participated in financial self-learning. On a five-point Likert scale (not at all important: very important), respondents felt that financial independence (4.7 ± 0.8) and their finances (4.7±0.8) were important for their well-being. Additionally, they valued being prepared for retirement (4.7±0.9). Regarding perceived financial literacy (very uncomfortable: very comfortable), respondents had the lowest comfort level with investing in the stock market (2.7±1.5), applying for a mortgage (2.8±1.6), and managing their retirement (3.0±1.4). Residents scored significantly lower than attendings on the financial literacy test (70.8% vs 79.6%, P<0.01), and residents scored lower on questions pertaining to investment (78.8% v 88.9%, P<0.01) and insurance and taxes (47.0% v 70.8%, P<0.01). Overall, respondents scored lower on questions about retirement (58.8%, P<0.01) and insurance and taxes (54.7%, P<0.01). Conclusion: Emergency physicians’ value of financial literacy exceeded confidence in financial literacy, and residents reported poorer confidence than attendings. We identified deficiencies in emergency physicians’ financial literacy for retirement, insurance, and taxes.